Cervical Ectopic Pregnancy: A case report and review of literature - Gabriel Dogbanya; Stephen Ajani; Festus Ogudugu; Zaro Boysungni; Samuel Ilikannu; Offiong Ekeng (Babcock University Medical Journal)
Background: Cervical ectopic pregnancy is a rare obstetric emergency commonly associated with adverse outcomes because of the diagnostic and treatment challenges it poses.